Discerning goodness of leaders using thin-sliced judgement of nonverbal cues among lay Malaysian and Chinese perceivers - Ahmed Hashmi, Madiha (2016)
The notion of goodness is implicitly central to the discourse relating to person perception. Research indicates that nonverbal cues greatly influence person perception. In addition, ‘thin slice studies’ (brief observation of nonverbal cues) have demonstrated that accurate personality appraisals of unknown others can be made at above than chance levels. To date no study has delved explicitly into the notion of goodness while forming rapid and unreflective inferences about others via nonverbal cues. The purpose of this study was twofold: to explore if accurate thin-sliced judgments of politicians’ goodness could be made by politically naïve audiences –relying solely on nonverbal cues. Also, to understand how lay audiences perceive politicians through their nonverbal demeanor based on thin-sliced snapshots. Performed in two phases, the study applied a qualitative research design by utilizing focus group interviews. In the first stage, six focus group sessions were conducted -three focus groups comprising of Malaysian students and three focus groups comprising of Chinese students. These focus groups helped uncover the meanings and associations related to ‘goodness’ across the two collectivist cultures. In the second stage, politically naïve participants made impressionistic judgments about select politicians’ perceived goodness – which was established through media reports. Study participants viewed brief glimpses of politicians while delivering speeches and were asked to make snap impressionistic judgments about the target stimuli, with a particular focus on the goodness element, followed by a discussion probing the rationale behind their evaluations. Focus group participants’ narratives were not entirely consistent across the spectrum. Perceivers were not able to form uniform judgments about all six politicians. That said, it is noteworthy that participants were still able to form fairly accurate impressions of some politicians based on brief glimpses of nonverbal footage. These contradictory findings are discussed and analyzed in the discussion section of this dissertation. The purpose of this study was also to examine the nonverbal indicators of goodness as articulated by the participants after forming rapid thin sliced judgments. Across all the groups, paralinguistic cues (pace and pause in speech), dynamic cues (gestures and face/eye behavior) and static cues (appearance/features and age) were found to be instrumental in the formation of accurate perceptions of goodness based on thin slices of non-verbal cues. These findings have important implications for the areas of nonverbal behavior, political communication and personality judgment.